An offer to centralize the public contracting of road infrastructure in Bogota D.C 2015 (2015)
he contracting in Colombia has been an object of study and regulation acquiring special importance from the year 1976, the current contracting and specifically in the city of Bogota it has had big technological and administrative advances that seek to satisfy the social needs and likewise to guarantee the investments of the city with a political and social control that does not generate any more corruption.